Recovery after Delayed Surgery in a Case of Spinal Subdural Hematoma - Pier Paolo Panciani; Claudio Cornali; Alessandro Agnoletti; Giacomo Esposito; Gabriele Ronchetti; Marco Fontanella (Case Reports in Neurological Medicine)
Spinal chronic subdural hematoma (SCSH) is a rare pathology usually associated with trauma or hematological alterations or is due to iatrogenic causes; rarely SCSH can be spontaneous. We report a case of a 79-year-old female who underwent a surgical evacuation of a spontaneous SCSH one year after diagnosis. She presented with a severe paraparesis and showed a considerable improvement in sensory-motor performances after surgery. The treatment of spontaneous SCSH is not well defined and universally accepted. Early surgery is mandatory in cases presenting with severe deficits. To the best of our knowledge, this is the first case showing a good outcome in a case of SCSH following a delayed surgery. In our opinion, an aggressive approach should be considered as a viable option in cases of spontaneous SCSH even after a lasting spinal cord compression.